2003
DOI: 10.1038/sj.bjc.6600673
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for malignant pleural mesothelioma: past results and recent developments

Abstract: This review summarises the results of previously conducted clinical trials, and subsequently presents data arising from all phase II -III studies on chemotherapy of malignant pleural mesothelioma (MPM) published since the last relevant overview. While response rates exceeding 30% have barely been achieved with established cytotoxic drugs in MPM therapy, novel chemotherapeutic agents and their combinations appear more promising. This applies especially to the antimetabolites, and in particular to pemetrexed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 80 publications
(27 reference statements)
0
26
0
Order By: Relevance
“…Gemcitabine and pemetrexed have already been shown to be particularly effective in combination with cisplatin for MMe chemotherapy. 29 We therefore tested the cytotoxic effect induced by these two agents in the presence of different concentrations of imatinib. As expected, gemcitabine and pemetrexed killed MMe cells in a dose-dependent manner.…”
Section: Effect Of Imatinib On Viability Of Mme Cells Expressing Pdgfrbmentioning
confidence: 99%
See 1 more Smart Citation
“…Gemcitabine and pemetrexed have already been shown to be particularly effective in combination with cisplatin for MMe chemotherapy. 29 We therefore tested the cytotoxic effect induced by these two agents in the presence of different concentrations of imatinib. As expected, gemcitabine and pemetrexed killed MMe cells in a dose-dependent manner.…”
Section: Effect Of Imatinib On Viability Of Mme Cells Expressing Pdgfrbmentioning
confidence: 99%
“…Combined treatment with cisplatin/pemetrexed and cisplatin/gemcitabine have been found to be more effective than each single agent used alone. 29 The aim of the present study is to investigate a translational approach which assesses the possible efficacy of imatinib as a single agent and in combination treatment for MMe.…”
mentioning
confidence: 99%
“…Mesothelioma is a chemoresistant malignancy. Only multimodality regimens of treatment, based on surgery, radiotherapy and chemotherapy, improve the long-term survival for a very small subgroup of patients (Jaklitsch et al, 2001;Tomek et al, 2003). Furthermore, it has been shown that MM patients have impaired immune responsiveness (Manning et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…MM cells exhibit resistance in vitro and in vivo to many anti-cancer agents, including doxorubicin and cisplatin, which are nevertheless widely used to treat MM (4). In most cases, this is the consequence of overexpression of the ATP-binding cassette (ABC) transporters, including MDR1 (ABCB1), MRP1 (ABCC1), and MRP2 (5).…”
Section: Malignant Mesothelioma (Mm)mentioning
confidence: 99%